Neurite branch retraction is caused by a threshold-dependent mechanical impact - Franze, Kristian; Gerdelmann, Jens; Weick, Michael; Betz, Timo; Pawlizak, Steve; Lakadamyali, Melike; Bayer, Johannes; Rillich, Katja; Goegler, Michael; Lu, Yun-Bi; Reichenbach, Andreas; Janmey, Paul; et al. (Biophysical Journal, 2009)
Recent results indicate that, in addition to chemical cues, mechanical stimuli may also impact neuronal growth. For instance, unlike most other cell types, neurons prefer soft substrates. However, the mechanisms responsible for the neuronal affinity for soft substrates have not yet been identified. In this study, we show that, in vitro, neurons continuously probe their mechanical environment. Growth cones visibly deform substrates with a compliance commensurate with their own. To understand the sensing of stiff substrates by growth cones, we investigated their precise temporal response to well-defined mechanical stress. When the applied stress exceeded a threshold of 274±41 pN/μm2, neurons retracted and re-extended their processes, thereby enabling exploration of alternative directions. A calcium influx through stretch-activated ion channels and the detachment of adhesion sites were prerequisites for this retraction. Our data illustrate how growing neurons may detect and avoid stiff substrates - as a mechanism involved in axonal branch pruning - and provide what we believe is novel support of the idea that mechanics may act as guidance cue for neuronal growth. © 2009 by the Biophysical Society.
CRIS-Team Scopus Importer:2020-08-12